Dynamics of Public Administration in Indonesia: Comparison Between Formal and Informal Sectors - Syafaruddin Syafaruddin (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
This research explores the dynamics of public administration in Indonesia by comparing the roles and interactions of the formal and informal sectors in service delivery. Utilizing a qualitative approach, the study examines how these two sectors function independently and collaboratively within the broader context of governance. Data were collected through semi-structured interviews and focus group discussions with stakeholders from both sectors, including government officials, community leaders, and informal service providers. The findings reveal that while the formal sector is essential for providing structured public services and ensuring accountability, it often faces challenges such as bureaucratic inefficiencies and limited responsiveness to local needs. In contrast, the informal sector plays a critical role in addressing gaps left by formal institutions, offering agile and community-driven solutions, particularly in underserved areas. However, the informal sector also encounters significant challenges, including a lack of recognition and resources, which can hinder its effectiveness. The study highlights the importance of fostering collaboration between the formal and informal sectors to enhance public service delivery. By integrating the strengths of both sectors, it is possible to create a more responsive and effective public administration system. The research emphasizes that recognizing and supporting the informal sector as a complement to the formal sector is crucial for improving governance outcomes in Indonesia. The study provides actionable recommendations for policymakers to promote synergy between these sectors, ultimately leading to better public services that meet the diverse needs of the Indonesian population.